IDENTITAS NASIONAL SUATU BANGSA DAN NEGARA SERTA PERANAN PENTING KONSTITUSI DALAM KEHIDUPAN BERNEGARA - Banna Nidham Ulhaq Banna; Isa Anshori (Prodi PPkn Universitas Slamet Riyadi, 2022)
National identity is a sign or characteristic of a country that can distinguish its characteristics from other countries, because the identity of a country lies in the concept of the country itself. Etymologically, national identity comes from the words